The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000026343
|View full text |Cite
|
Sign up to set email alerts
|

Increased photokeratitis during the coronavirus disease 2019 pandemic

Abstract: An increased incidence of photokeratitis has occurred during the coronavirus disease 2019 (COVID-19) pandemic due to improper and unprotected use of ultraviolet lamps. Here, we summarize the clinical and epidemiological features of this increased incidence of photokeratitis and share advice in using health education to prevent it. We collected data from patients diagnosed with photokeratitis from October 7, 2019 to December 1, 2019, and from February 17, 2020 to April 12, 2020, and compared the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…Nearly half of respondents who owned a lamp experienced a side-effect (48%, n = 19), which is consistent with existing research that has reported side-effects after exposure to UV-C (12,14,15). One reason these devices could be associated with adverse side-effects is because of generally higher irradiance and that the access to direct UV exposure of skin and eye are not prevented by design consideration, that is they are free-standing open sources, unlike other device types.…”
Section: Wave 4-reported Side-effects Analysis and Misattributionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nearly half of respondents who owned a lamp experienced a side-effect (48%, n = 19), which is consistent with existing research that has reported side-effects after exposure to UV-C (12,14,15). One reason these devices could be associated with adverse side-effects is because of generally higher irradiance and that the access to direct UV exposure of skin and eye are not prevented by design consideration, that is they are free-standing open sources, unlike other device types.…”
Section: Wave 4-reported Side-effects Analysis and Misattributionsupporting
confidence: 88%
“…However, the relative benefit of using portable UV-C devices to reduce the risk of COVID-19 transmission in individual settings, compared to other mitigation measures, is still unknown (8). Moreover, despite the potential benefit of virus inactivation (9), case studies report that excessive UV-C exposure to the eyes and skin can lead to side-effects, namely eye pain (photokeratitis) and skin rash (erythema), in the workplace (10)(11)(12)(13)(14), home (12,15) school (16)(17)(18) and clinical settings (19,20). The extent to which ultraviolet radiation may induce these side-effects is dependent on the wavelength of UV radiation, the dose of UV radiation and the susceptibility of the individual (7,21,22).…”
Section: Introductionmentioning
confidence: 99%